The The Effectiveness Using Pictionary Game Toward Students Vocabulary Mastery - Nurul Mufarida; Ainu Zunrudiana; Nurul Mufarida; Ainu Zunrudiana (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
The purpose of this research is to know whether use of Pictionary game effectives on students vocabulary mastery of class IV students at SDN Gajah 2 who found it difficult to mastering vocabulary and have a low score in vocabulary learning. The grand theory of the research is based on the Game as an Education Theory by Harmer and Lely. The technique used in this research is Pictionary game. In this research, Researcher used one-group pertest post test experimental research design that was conducted in 4 meetings. In this research, Researcher use instrument in the form of observation and test to collect data with count of participant is 14 students. This research demonstrate that Pictionary game is effective on students vocabulary mastery, the results of observation showed that teacher has implemented process using the Pictionary game well, students showed positive responses and students abilities progressed well in each meeting. Meanwhile the results of the paired sample t-test show that alternative hypothesis (Ha) was accepted because T-count > T table which 2.810 > 2.160 with significance effect 0.05 means that Pictionary game is effective toward students vocabulary mastery of SDN Gajah 2 students.